Effects of Lactiplantibacillus plantarum DSM 33464 in children with elevated blood lead levels: a randomized, double-blind, placebo-controlled study - Ji, Wenjing; Saulnier, Delphine Marie; Zhang, Lan; Liu, Jingxia; Gao, Jisheng; Wang, Xia; Holz, Caterina; Liang, Aimin; Tan, Hern-Tze Tina (Frontiers in Nutrition, 2025)
IntroductionApproximately one-third of the world’s children have elevated blood lead levels (BLLs), which may lead to often-irreversible decreased intelligence, behavioral difficulties, and learning problems. Identification and removal of the source of lead, along with good nutrition, are the only advocated initial management, with chelation therapy for higher threshold BLLs. Probiotics have shown promising beneficial effects pre-clinically. Here, we investigated the safety and efficacy of the probiotic Lactiplantibacillus plantarum DSM 33464 in children with elevated blood lead levels.MethodsChildren aged 3–12 years with elevated BLLs (>3.5 μg/dL) were enrolled in a randomized double-blind placebo-controlled multi-centered study and received either probiotic (1 × 109) colony-forming units (CFUs) or placebo (control group), along with a multivitamin/mineral supplement in both groups daily for 12 weeks.ResultsOverall, 66 children were randomized, 54 received intervention (probiotic; n = 30 and control; n = 24). The probiotic was well-tolerated. Probiotics, combined with a multivitamin/mineral supplement, significantly reduced the BLLs in these children within 12 weeks of supplementation by 40%, similar to that of the control group, which received a placebo plus multivitamin/mineral supplement. A larger reduction in urine lead levels at 8 weeks was observed in the probiotic group, along with a reduction of abdominal pain and psychosomatic feelings at week 12. No depletion of essential minerals was observed in any of the groups.ConclusionThis study adds to previous findings suggesting that probiotic intervention may be a promising additional strategy to help reduce BLLs and their detrimental effects in children. Due to the preliminary nature of this study, larger studies investigating the effects of the strain alone, with a longer intervention period, are warranted to confirm the benefits observed.Clinical trial registrationClinicaltrials.gov, identifier NCT04891666.